2017
DOI: 10.1037/adb0000244
|View full text |Cite
|
Sign up to set email alerts
|

The proximal effects of acute alcohol use on female aggression: A meta-analytic review of the experimental literature.

Abstract: Experimental research on alcohol-related aggression has focused largely upon male participants, providing only a limited understanding of the proximal effects of acute alcohol use on aggression among females extrapolated from the male literature. The current meta-analysis was undertaken to summarize the effects of alcohol, compared to placebo or no alcohol, on female aggression as observed across experimental investigations. Method. A review of the literature yielded 11 articles and 12 effect sizes for further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 53 publications
3
68
1
Order By: Relevance
“…A preponderance of survey data strongly suggests that partner violent male participants evidence patterns of greater alcohol consumption than nonviolent male participants within concurrent assessment periods . The association between alcohol and traditional IPV emerges among female samples as well, though the cumulative effect appears smaller than that observed among male samples . Researchers have advanced etiological models to postulate a mechanism by which problematic alcohol use and traditional IPV are related.…”
Section: Alcohol and Traditional Ipvmentioning
confidence: 99%
“…A preponderance of survey data strongly suggests that partner violent male participants evidence patterns of greater alcohol consumption than nonviolent male participants within concurrent assessment periods . The association between alcohol and traditional IPV emerges among female samples as well, though the cumulative effect appears smaller than that observed among male samples . Researchers have advanced etiological models to postulate a mechanism by which problematic alcohol use and traditional IPV are related.…”
Section: Alcohol and Traditional Ipvmentioning
confidence: 99%
“…Research has shown alcohol-related impairments to emotional affect, empathy, and interpersonal skills. For example, alcohol intoxication has been linked to increased risk for engaging in violent behavior (e.g., Giancola et al, 2011), as well as for demonstrating indirect aggression such as social manipulation or bullying (Crane, Licata, Schlauch, Testa, & Easton, 2017). In a study of bystander intervention, Sheehan, Linden-Carmichael, and Lau-Barraco (2016) were able to demonstrate both that alcohol intoxication was linked to an increased risk for participating in sexual violence, and that men who met the criteria for heavy drinking were also less likely to intervene when witnessing a sexually violent act in comparison to their peers who consumed less alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies have consistently found an effect of intoxication on analogues of human aggression, although the majority of these studies have only examined male to male aggression. Crane, Godleski, Przybyla, Schlauch and Testa , however, found a significant effect of alcohol in a meta‐analysis of all alcohol‐aggression experiments in which alcohol was administered to men and aggression toward a woman was assessed.…”
mentioning
confidence: 95%